Penerapan Thought Stopping terhadap Penurunan Derajat Keparahan Psoriasis - Eka Kusumawati; Aniska Indah Fari; Veroneka Y. Windahandayani (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2026)
Psoriasis is a chronic inflammatory skin disease influenced by psychological factors such as stress and negative thoughts that may exacerbate recurrence. Patients often experience anxiety, overthinking, and sleep disturbances, affecting clinical stability. This study aimed to analyze the implementation of nursing care using the thought stopping technique to reduce psychological stress and maintain psoriasis stability. A case study design was applied to three patients with varying severity levels. The intervention was conducted over two months through several sessions with periodic evaluation. Data were collected using nursing assessment, the Perceived Stress Scale-10 (PSS-10), and clinical observation. The findings showed a decrease in stress and anxiety levels in all patients, with no worsening of clinical conditions during the intervention period. Subjective complaints such as itching were reduced, and skin conditions remained stable. The implementation of this intervention implies that thought stopping can be used as an effective non-pharmacological nursing approach to manage psychological stress and support clinical stability in psoriasis patients.